Modulation of Replicative Lifespan in Cryptococcus neoformans: Implications for Virulence - Bouklas, Tejas; Jain, Neena; Fries, Bettina C. (Frontiers in Microbiology, 2017)
The fungal pathogen, Cryptococcus neoformans, has been shown to undergo replicative aging. Old cells are characterized by advanced generational age and phenotypic changes that appear to mediate enhanced resistance to host and antifungal-based killing. As a consequence of this age-associated resilience, old cells accumulate during chronic infection. Based on these findings, we hypothesized that shifting the generational age of a pathogenic yeast population would alter its vulnerability to the host and affect its virulence. SIR2 is a well-conserved histone deacetylase, and a pivotal target for the development of anti-aging drugs. We tested its effect on C. neoformans’ replicative lifespan (RLS). First, a mutant C. neoformans strain (sir2Δ) was generated, and confirmed a predicted shortened RLS in sir2Δ cells consistent with its known role in aging. Next, RLS analysis showed that treatment of C. neoformans with Sir2p-agonists resulted in a significantly prolonged RLS, whereas treatment with a Sir2p-antagonist shortened RLS. RLS modulating effects were dependent on SIR2 and not observed in sir2Δ cells. Because SIR2 loss resulted in a slightly impaired fitness, effects of genetic RLS modulation on virulence could not be compared with wildtype cells. Instead we chose to chemically modulate RLS, and investigated the effect of Sir2p modulating drugs on C. neoformans cells in a Galleria mellonella infection model. Consistent with our hypothesis that shifts in the generational age of the infecting yeast population alters its vulnerability to host cells, we observed decreased virulence of C. neoformans in the Galleria host when RLS was prolonged by treatment with Sir2p agonists. In contrast, treatment with a Sir2p antagonist, which shortens RLS enhanced virulence in Galleria. In addition, combination of Sir2p agonists with antifungal therapy enhanced the antifungal’s effect. Importantly, no difference in virulence was observed with drug treatment when sir2Δ cells were used for infection, which confirmed target specificity and ruled out non-specific effects of the drugs on the Galleria host. Thus, this study suggests that RLS modulating drugs, such as Sir2p agonists, shift lifespan and vulnerability of the fungal population, and should be further investigated as a potential class of novel antifungal drug targets that can enhance antifungal efficacy.